Pengaruh Profitabilitas, Ukuran Perusahaan, Tingkat Leverage, Pertumbuhan, dan Likuiditas Terhadap Kebijakan Dividen Perusahaan Non-Finansial Di Indonesia Tahun 2012-2016 - Judith Wijaya; Yulius Jogi Christiawan (Business Accounting Review, 2018)
There was inconsistency results of the previous research on the affects of profitability, firm size, leverage, growth, and liquidity on dividend policy. This study aimed to obtain evidence empirically of the affect of profitability, firm size, leverage, growth, and liquidity on dividend policy. The sample used in this study was non-financial companies listed in the Indonesia Stock Exchange in period of 2012-2016. The number of companies according to the sample criteria chosen by purposive sampling method was, in 2012 was 144 companies, in 2013 was 142 companies, in 2014 was 148 companies, in 2015 was 136 companies, and in 2016 was 153 companies. The data analysis method used was multiple linear regression test by using SPSS program. The results showed that profitability and firm size had significant positive affect on dividend policy, while leverage and growth had significant negative affect on dividend policy, and liquidity had no effect on dividend policy.